PERBEDAAN DEPRESI PADA IBU HAMIL DENGAN DEPRESI PADA IBU POSTPARTUM TERHADAP KESIAPAN PERAN MENJADI IBU DI RSIA BUNDA ARIF PURWOKERTO - Devi Irmaning Tyas; Atun Raudotul Ma’rifah; Noor Yunida Triana (Viva Medika, 2015)
Pregnancy, childbirth, and being a mother is a womenâ€™s physiological. These event are the transition of womenâ€™s life. In some women, the transition can cause stress that resulting negativething, feeling scared and depression to her new life. Mother who experienced depression caninfluence readiness role being mother at Mother and Child Hospital Bunda Arif Purwokerto in2013. This type of research is comparative study with was crosss sectional approach. Thetechnique of sample interpretation used purposive sampling with 68 sample consist of 34pregnant women and 34 postpartum women.The instrument of this research were BDI IIâ€™squestionnaire, EPDSâ€™s questionnaire, and the readiness of role questionnaire that has already putto a test according to validity and realibility using correlation of product moment. Data analysisuse test U Mann Whitney, it is test that comparing 2 independent group. The conclusion of research is there are differences depression in pregnant women anddepression in postpartum women in the case of readiness role being mother in Mother and ChildHospital Bunda Arif Purwokerto with Ï value = 0,000. Therefore pregnant women andpostpartum women are expected to increase knowledge about pregnancy and maternity so thatthey have information about the things that must be prepared related to their role as a mother. Key words : depression, pregnant women, postpartum women/ maternal, the readiness of therole of being a mother